#1**0 **

Since you are starting at -4,2 and going to 12, you are going in a positive direction, so your answer will be positive.

The formula is (final location) - (starting location)

= (1.2) - (-4.2)

= 1.2 + 4.2

= 5.6

geno3141 Jan 30, 2020

#2**0 **

-----

Hi there...

You started off well, but you came to the wrong conclusion.

"(-4.2 + 5.6)=1.4"

While...

"(1.2 - -4.2)=5.4"

In other words...

"(1.2 - 5.4)=-4.2"

Question...: "How can I get to 1.2 form -4.2?"

Answer...: "(-4.2 + 5.4)=1.2"

I hope that cleared things up a bit?

Kind regards

BizzyX

-----

BizzyX
Jan 31, 2020